The Japanese Advantage? / The It Battleground in Europe - Hunt Brian; Targett David (Butterworth Heinemann, 1995)
This book is of great interest to IT strategists and managers, as well as to MBA-level students and management academics with an interest in this fast-moving and dynamic area. Preface, Acknowledgements, Setting the Scene, Competition Between Japanese and Western Organizations, The Strategic Role of Information Technology, Japanese Culture and Japanese Management, Case Studies, All Nippon Airways Ltd, Daiwa Europe Ltd, Hitachi Europe Ltd, JVC (UK) Ltd, Kobe Steel Europe Ltd, Nissan Motor (GB) Ltd, Nissan Motor Manufacturing (UK) Ltd, Sony (UK) Ltd, Toshiba Information Systems (UK) Ltd, Weighing the Evidence, Japanese Management of IT, The Business Impact and Strategic Use of IT, Head Office Control, Eclipsing the Sun?, Index.